For Love or Money? Fairtrade Business Models in the UK Supermarket Sector - Smith, Sally (Journal of business ethics, 2010)
Sales in supermarkets have contributed greatly to growth in Fairtrade, but the literature suggests there may be tensions between Fairtrade principles and the commercial practices which characterise UK supermarket value chains. This article explores these tensions through an analysis of supermarket value chains for Fairtrade coffee, cocoa, bananas and fresh fruit. It finds considerable variation in UK supermarket approaches in terms of scale and scope of commitment to Fairtrade and in the nature of relationships with Fairtrade suppliers. In some cases supermarket involvement has the potential both to expand and deepen the impact of Fairtrade, whereas in others it threatens to undermine the ability of Fairtrade to support long-term processes of development. The findings indicate that a more nuanced approach to supermarket Fairtrade is required, with recommendations for actions that could be taken to maximise the opportunities and minimise the risks.